Perlindungan Hukum Bagi Justice Collaborator Dalam Undang-Undang Narkotika - Mahfud Mahfud (Fakultas Hukum Universitas Muhammadiyah Aceh, 2018)
Indonesia has introduced justice collaborator protection as a perpetrator who iscooperating with the law enforcers to probe certain cases. However, the protection of justice collaborator has not been optimal yet including who involved in narcotic cases. This Article aims to review the kinds of law protection for them in Indonesian narcotic cases. This is normative legal research by exploring books, laws, and relevant scientific articles. The protection that are provided are guarantees from physical, soul, and property from the beginning till the end of criminal processes with the conditions that the perpetartor has admitted that he comitted the crime, he is not the principal perpetartor and he agrees to provide information in the trial process. It is suggested that they are comprehensively protected and punished with the probation and the LPSK should be granted wider power and to be more independent body.